Analyzing Students’ Difficulties in Learning Nahwu and Effective Pedagogical Solutions: A Psycholinguistic Approach - Baharun, Segaf (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
The study of nahwu (Arabic grammar) is fundamental for learners of Arabic as a second or foreign language. However, many students struggle with understanding and applying nahwu rules due to cognitive overload, first-language interference, and psychological barriers such as grammar anxiety and lack of motivation. This study examines these challenges through a psycholinguistic perspective and explores effective pedagogical strategies to enhance nahwu acquisition. Using a mixed-methods approach, integrating both quantitative and qualitative methods to analyze students' difficulties in learning nahwu and explore effective pedagogical solutions through a psycholinguistic perspective, data were collected from 60 students at Pondok Pesantren Darullughah Wadda’wah through diagnostic grammar tests, psycholinguistic surveys, semi-structured interviews, and classroom observations. The findings indicate that mnemonic storytelling and contextual learning significantly improve students' comprehension and retention of nahwu rules compared to traditional rote learning. Students exposed to these methods demonstrated higher engagement and reduced cognitive strain, leading to better application of grammatical structures. This study contributes to Arabic language pedagogy by integrating cognitive and affective dimensions into nahwu instruction. It underscores the importance of reducing cognitive load, employing interactive learning techniques, and fostering emotional engagement to enhance nahwu mastery. Future research should explore the long-term effects of psycholinguistic interventions and the role of AI-driven adaptive learning in optimizing Arabic grammar education.